SISTEMATIK LITERATUR REVIEW (SLR) : ANALISIS PESAN DAKWAH DALAM FILM “TUHAN IZINKAN AKU BERDOSA” - Yuliana Sulistyaningtyas; Batsnah Nuwaifila Batsnah Nuwaifila; Cinarsih Cinarsih; Muhammad Rikzam Kamal Muhammad Rikzam Kamal (Jurnal Komunikasi dan Media, 2025)
The film "God Allows Me to Sin" is a film directed by Hanung Bramantyo and in it raises an unusual religious story and the issue of sexual harassment experienced by a female student who is intelligent and grew up in a family with strong religious beliefs. The religious story in it is what makes the researcher interested in studying more deeply from the perspective of da'wah. Therefore, the researcher reviewed 4 journals that reviewed this film. The method chosen in this study is a qualitative approach with a Systematic Literature Review (SLR) design which is carried out in several stages including; 1) Asking questions 2) Study findings 3) Critical evaluation of study findings 4) Data collection 5) Data analysis and reporting. This research results that in the film "God Allows Me to Sin" effectively represents the message of da'wah and Islamic values through the narrative of inner conflict, criticism of hypocrisy, and the challenge of da'wah in the modern era. Through a strong visual approach and complex main characters, this film proves that film media can be a means of communicative, inspiring, and relevant da'wah to convey moral messages and religious reflections to the wider community, especially the younger generation.